A Mulher no sistema carcerário : violência institucionalizada na sociedade de classes - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
This master's thesis seeks to analyze women in the prison system and institutionalized violence in class society, considering a critical and radical perspective on these issues. Despite the ever-present crises of the prison system, we reflect on gender violence, the capitalist mode of production and the punitive discourse and thought of general society. Such aspects and the researcher's performance contributed to outline the objectives of this research. Interpretative interviews were used and we selected five women who were that time in prison at the Consuelo Nasser Women's Penitentiary at Aparecida de Goiânia Prison Complex to answer a questionnaire. From questions about the values and the imprisonment of these women, it was possible to perceive and recognize the arrest of women as another form of violence, male domination over the female sex and maintenance of the patriarchy and capitalist system.
Women in the prison system: instititutionalized violence in class society
Keywords: Criminologia crítica; Encarceramento - Gênero feminino; Criminologia crítica - Mulheres; CIENCIAS HUMANAS::SOCIOLOGIA